Impacts of COVID-19 on agricultural production and food systems in late transforming Southeast Asia: The case of Myanmar. (March 2021) - Boughton, Duncan; Goeb, Joseph; Lambrecht, Isabel; Headey, Derek; Takeshima, Hiroyuki; Mahrt, Kristi; Masias, Ian; Goudet, Sophie; Ragasa, Catherine; Maredia, Mywish K.; Minten, Bart; Diao, Xinshen
Abstract: The objective of this contribution is to report the initial impacts of measures taken to contain the COVID-19 pandemic on Myanmar's agri-food system. Myanmar is one of several late-transforming low-income countries in Southeast Asia where agriculture still plays a large role in rural livelihoods, and where food prices are a key factor affecting nutrition security for poor urban and rural households. Whereas the economic impacts of COVID-19 disruptions on tourism and manufacturing were obvious to policymakers, the impacts on the agri-food system were less evident and often more indirect. This resulted in the rural sector being allocated only a very small share of the government's initial fiscal response to mitigate the economic impacts of COVID-19. To correct this information gap, a suite of phone surveys covering a wide spectrum of actors in the agri-food system were deployed, including farm input suppliers, mechanization service providers, farmers, commodity traders, millers, food retailers and consumers. The surveys were repeated at regular intervals prior to and during the main crop production season which began shortly after nationwide COVID-19 prevention measures were implemented in April. While the results indicate considerable resilience in the agri-food system in response to the initial disruptions, persistent financial stress for a high proportion of households and agri-food system businesses indicate that the road to a full recovery will take time. The experience provides important lessons for strengthening the resilience of the agri-food system, and the livelihoods of households that depend on it. Highlights: Myanmar has diverse agro-ecologies and agricultural production systems. Panel phone survey monitoring at multiple stages of the agrifood system Majority of farm households lost income due to COVID-19. Farm household coping strategies result in reduced savings and higher debt. COVID-19 health restrictions disrupted every aspect of the agrifood system.